2016
DOI: 10.1002/med.21384
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐Regulated Key Components of Cytokine Signaling Pathways and Inflammation in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an inflammatory disease that primarily affects joints. This autoimmune disease pathogenesis is related to cytokine signaling. In this review, we have described the existence of various microRNAs (miRNAs) involved in regulation of major protein cascades of cytokine signaling associated with RA. Moreover, we have tried to portray the role of various miRNAs in different cytokines such as TNF‐α, IL‐1, IL‐6, IL‐10, IL‐17, IL‐18, IL‐21, and granulocyte macrophage colony‐stimulating facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 75 publications
(128 reference statements)
1
52
0
Order By: Relevance
“…MiR-146a, a member of the class of miRNAs, has been found to participate in the pathogenesis of autoimmune diseases such as rheumatoid arthritis (RA), Osteoarthritis (OA), systemic lupus erythematosus (SLE), multiple sclerosis (MS) and GO [3, 9-13]. For instance, MiR-146a was reported to induce TNF-α production by targeting TNF-α/TNF receptor-associated factor 6 (TRAF6)/IL-1 receptor-associated kinase 1 (IRAK1) signaling in RA [14]. Again, miR-146a was reported to down-regulate IL-6 production in orbital fibroblasts [15].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-146a, a member of the class of miRNAs, has been found to participate in the pathogenesis of autoimmune diseases such as rheumatoid arthritis (RA), Osteoarthritis (OA), systemic lupus erythematosus (SLE), multiple sclerosis (MS) and GO [3, 9-13]. For instance, MiR-146a was reported to induce TNF-α production by targeting TNF-α/TNF receptor-associated factor 6 (TRAF6)/IL-1 receptor-associated kinase 1 (IRAK1) signaling in RA [14]. Again, miR-146a was reported to down-regulate IL-6 production in orbital fibroblasts [15].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] On the other hand, miRNA- 146a is also able to regulate gene such FAF1, IRAK2, FADD, IRF-5, Stat-1, and PTC-1. [21] In arthritis mouse model, intravenous administration of double stranded miR-146a suppresses of cartilage and bone destruction. [20] These demonstrated that miR-146a may be involved in inflammatory responses in RA.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Accumulating evidences have proven that several miRNAs have established their value on the progress of various immune diseases, including RA, systemic lupus erythematosus (SLE), and psoriasis, which uncovered the potential of miRNA as marker for RA progression and prognosis. [9][10][11][12][13][14][15] However, no studies investigate the effect of comprehensive miRNA expression profile on predicting clinical response to TNF inhibitor in RA patients. Thus, in the present study, the aim was to explore the correlation of circulating miRNA expression profile with clinical response to TNF inhibitor in treating active RA patients.…”
Section: Introductionmentioning
confidence: 99%